2015
DOI: 10.1073/pnas.1509754112
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) polymerase 1 is a novel target to promote axonal regeneration

Abstract: Therapeutic options for the restoration of neurological functions after acute axonal injury are severely limited. In addition to limiting neuronal loss, effective treatments face the challenge of restoring axonal growth within an injury environment where inhibitory molecules from damaged myelin and activated astrocytes act as molecular and physical barriers. Overcoming these barriers to permit axon growth is critical for the development of any repair strategy in the central nervous system. Here, we identify po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 58 publications
1
42
1
Order By: Relevance
“…1 A– D, P = 0.0004 a soluble and P = 0.0032 b insoluble). This PARylation increase is similar to that described in Brochier et al (2015). After 5 d of veliparib administration to naive mice, the level of PARylated protein was suppressed within the retinal tissue (Fig.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…1 A– D, P = 0.0004 a soluble and P = 0.0032 b insoluble). This PARylation increase is similar to that described in Brochier et al (2015). After 5 d of veliparib administration to naive mice, the level of PARylated protein was suppressed within the retinal tissue (Fig.…”
Section: Resultssupporting
confidence: 86%
“…One study found that PARP activity was required for inhibitory factors such as Nogo and MAG to limit axon outgrowth in cultured neurons (Brochier et al, 2015). Further, PARP itself was found to be upregulated by CNS injury, suggesting it might function in axon regeneration (Brochier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure of neurons to growth-limiting molecules, such as myelin-derived Nogo, myelin-associated glycoprotein (MAG) and chondroitin sulfate proteoglycans (CSPGs), activates the enzyme polymerase 1 (PARP1), causing the accumulation of poly(ADP-ribose), which limits axon growth 84 . Pharmacological inhibition or genetic deletion of PARP1 facilitates axon regeneration over non-permissive substrates in cultured cortical and DRG neurons by a mechanism that is independent of histone poly(ADP-ribosylation) (PARylation) or the activation of regeneration-associated genes (RAGs) 84 . This system is conserved across species, as removal of poly(ADP-ribose) from proteins by poly(ADP-ribose) glycohydrolases (PARGs) enhances axon regeneration in C. elegans neurons 85 .…”
Section: Injury Signallingmentioning
confidence: 99%
“…This system is conserved across species, as removal of poly(ADP-ribose) from proteins by poly(ADP-ribose) glycohydrolases (PARGs) enhances axon regeneration in C. elegans neurons 85 . Additionally, PARP is locally activated in the injured optic nerve 84 ; however, inhibition of PARP is insufficient to enhance axonal regeneration in either the optic nerve crush injury or thoracic spinal cord injury mouse models 86 . This is consistent with the fact that downstream of Nogo, MAG and CSPGs, other pathways cause growth cone collapse 87 .…”
Section: Injury Signallingmentioning
confidence: 99%